Analysis of student errors in reading and writing teaching (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Goals:This work aimed to analyze the reading and writing responses, the modification and the types of errors presented by students of a resource room during the exposure to a systematized and computerized reading and writing curriculum.Methodology: Data from nine students exposed to the program were analyzed. The responses identified as incorrect were categorized according to the literature and their frequency of occurrence across the program units was calculated.Results:The results showed a decrease in the incorrect responses, especially those that did not correspond to the target response, more present in the unit pre-test, and an increase in the occurrence of responses with higher correspondence to the target word, more present in post-tests.Conclusions:At the end of the program the participants' responses became more correspondent with the target word, even for those words not taught directly, demonstrating the effectiveness of the program in teaching recombinative reading.
Keywords: Verbal Behavior Analysis. Reading. Writing. Error analysis